Combined Effects of Three High-Energy Charged Particle Beams Important for Space Flight on Brain, Behavioral and Cognitive Endpoints in B6D2F1 Female and Male Mice - Raber, Jacob; Yamazaki, Joy; Torres, Eileen Ruth S.; Kirchoff, Nicole; Stagaman, Keaton; Sharpton, Thomas; Turker, Mitchell S.; Kronenberg, Amy (Frontiers in Physiology, 2019)
The radiation environment in deep space includes the galactic cosmic radiation with different proportions of all naturally occurring ions from protons to uranium. Most experimental animal studies for assessing the biological effects of charged particles have involved acute dose delivery for single ions and/or fractionated exposure protocols. Here, we assessed the behavioral and cognitive performance of female and male C57BL/6J × DBA2/J F1 (B6D2F1) mice 2 months following rapidly delivered, sequential irradiation with protons (1 GeV, 60%), 16O (250 MeV/n, 20%), and 28Si (263 MeV/n, 20%) at 0, 25, 50, or 200 cGy at 4–6 months of age. Cortical BDNF, CD68, and MAP-2 levels were analyzed 3 months after irradiation or sham irradiation. During the dark period, male mice irradiated with 50 cGy showed higher activity levels in the home cage than sham-irradiated mice. Mice irradiated with 50 cGy also showed increased depressive behavior in the forced swim test. When cognitive performance was assessed, sham-irradiated mice of both sexes and mice irradiated with 25 cGy showed normal responses to object recognition and novel object exploration. However, object recognition was impaired in female and male mice irradiated with 50 or 200 cGy. For cortical levels of the neurotrophic factor BDNF and the marker of microglial activation CD68, there were sex × radiation interactions. In females, but not males, there were increased CD68 levels following irradiation. In males, but not females, there were reduced BDNF levels following irradiation. A significant positive correlation between BDNF and CD68 levels was observed, suggesting a role for activated microglia in the alterations in BDNF levels. Finally, sequential beam irradiation impacted the diversity and composition of the gut microbiome. These included dose-dependent impacts and alterations to the relative abundance of several gut genera, such as Butyricicoccus and Lachnospiraceae. Thus, exposure to rapidly delivered sequential proton, 16O ion, and 28Si ion irradiation significantly affects behavioral and cognitive performance, cortical levels of CD68 and BDNF in a sex-dependent fashion, and the gut microbiome.